STRATEGIC IMPACT (SCAMPER) IN THE ACHIEVEMENT OF SCIENCE FOR SECOND-GRADE INTERMEDIATE STUDENTS - Zeena Saffah Abdelsattar; Dr. Majed Abdel Sattar Abdel Karim (Journals Park Publishing, 2022)
This study aimed to find out the effect of the strategy Scamper In the achievement of science for second-grade intermediate students, one of the intermediate schools (Umm Salamah Intermediate School for Girls) was chosen in Diyala Governorate, and the students were randomly divided to represent one of the two experimental groups and the other to represent the control group, and the research sample consisted of (60) female students. The experimental group included (30) and the control group (30). The course included four chapters (seventh, eighth , ninth , tenth), the behavioral objectives of the four chapters were formulated and amounted to (198) objectives for Bloom’s classification of the cognitive domain (remember, understanding, application, analysis, installation, evaluation), and preparing teaching plans for the two groups ( experimental and control), and it was (18) a teaching plan for the two groups. The test tool consists of an achievement test prepared by the researcher. It consists of (40) paragraphs of the type of multiple choice that contains four alternatives. The results were processed using the statistical package (SPSS) . The results showed that the experimental group outperformed the control group in achievement.
Keywords: strategy Scamper; collection